Three-dimensional finite-element analyses for radio-frequency hepatic tumor ablation - Tungjitkusolmun, Supan; Staelin, S. Tyler; Haemmerich, Dieter; Tsai, Jang Zern; Cao, Hong; Webster, John G.; Lee, Fred T.; Mahvi, David M.; Vorperian, Vicken R. (My University, 2002)
Radio-frequency (RF) hepatic ablation, offers an alternative method for the treatment of hepatic malignancies. We employed finite-element method (FEM) analysis to determine tissue temperature distribution during RF hepatic ablation. We constructed three-dimensional (3-D) thermal-electrical FEM models consisting of a four-tine RF probe, hepatic tissue, and a large blood vessel (10-mm diameter) located at different locations. We simulated our FEM analyses under temperature-controlled (90 °C) 8-min ablation. We also present a preliminary result from a simplified two-dimensional (2-D) FEM model that includes a bifurcated blood vessel. Lesion shapes created by the four-tine RF probe were mushroom-like, and were limited by the blood vessel. When the distance of the blood vessel was 5 mm from the nearest distal electrode 1) in the 3-D model, the maximum tissue temperature (hot spot) appeared next to electrods A. The location of the hot spot was adjacent to another electrode 2) on the opposite side when the blood vessel was 1 mm from electrode A. The temperature distribution in the 2-D model was highly nonuniform due to the presence of the bifurcated blood vessel. Underdosed areas might be present next to the blood vessel from which the tumor can regenerate.
Keywords: Bioheat equation; Finite-element analysis; Hepatic ablation; Radio-frequency ablation